SIMULTANEOUS MEASUREMENTS ON AN ICE ISLAND SURFACE AND 1000 FEET BELOW. - Heirtzler,J. R. (1963)
For a few weeks in the fall of 1962 the total geomagnetic field intensity was measured simultaneously on an ice island surface and approximately 1000 feet below. The magnetic gradient as indicated by the difference between the two readings varied as the station passed over geologic bodies. A statistical analysis of the time variations during two time intervals revealed an attenuation and phase shift of the lower head reading with respect to the surface head reading. The analysis was made between 70 and 400 seconds period. There are indications of an anomalous attenuation at the lower period end of this band although the experiment was not such that accurate determinations could be made. (Author)